Optical film, polarizing plate and organic electroluminescent image display device

By using an optical film containing a pigment compound with a specific structure and a cyclic olefin resin in an organic electroluminescent image display device, the problems of reflected light leakage and insufficient pigment light resistance are solved, and high transparency and durability are achieved. Suitable for applications under severe environmental conditions.

CN115136045BActive Publication Date: 2024-12-20KONICA MINOLTA INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202180016225.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-19
Publication Date
2024-12-20
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Prior Art In an organic electroluminescent image display device, the wavelength dispersion characteristics of the cyclic olefin resin lead to leakage of reflected light, and the light resistance of the pigment compound is insufficient, which affects the transparency and durability of the device.

Method used

Using compounds containing specific structures, such as pigment compounds having dicyano structures, combined with cyclic olefin resins, the optical film formed has high transparency and light resistance, and by reducing the highest orbital energy level of the pigment to suppress photooxidation , improve overall durability.

Benefits of technology

High transparency and light resistance under severe environmental conditions are achieved, reflected light leakage is reduced, and durability and brightness stability of the image display device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115136045B_ABST
    Figure CN115136045B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide an optical film which has high transparency and prevents light leakage when applied to an image display device, and which has excellent light resistance and durability under harsh environmental conditions, a polarizing plate having the optical film, and an organic electroluminescent image display device. The optical film of the present invention contains a thermoplastic resin, characterized in that it contains a compound having a structure represented by the following general formula (1). General formula (1) (wherein Z represents a heteroaryl group having two or more heteroatoms, which may have a substituent).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical film, a polarizing plate and an organic electroluminescent image display device, and more particularly to an optical film which has high transparency and prevents light leakage when applied to an image display device and has excellent light resistance and durability under severe environmental conditions. Background Art

[0002] In an organic electroluminescent (hereinafter also referred to as "organic EL") image display device, the external light reflection generated by the metal plate inside is significant, and an anti-reflection film combining a λ / 4 phase difference film and a polarizer is used. As the material of the phase difference film, if a cyclic olefin resin (hereinafter also referred to as "COP") is used, reflection leakage occurs at a specific wavelength due to the influence of its wavelength dispersion. Therefore, in order to suppress reflection leakage, it is necessary to assemble a layer containing a pigment that absorbs light of a specific wavelength (hereinafter also referred to as a "specific wavelength light absorption layer") into the display. As long as the specific wavelength light absorption layer is in the display, it can be set at any position, and can also be set to the λ / 4 phase difference film.

[0003] However, when a retardation film is produced by directly adding a dye to a resin, there is an interaction with the resin, and photodegradation of the dye may be promoted.

[0004] For example, Patent Document 1 discloses a method of adding a pigment that absorbs light with a wavelength near 400 nm to a pressure-sensitive adhesive layer in order to protect an organic EL element, and Patent Document 2 discloses a method of adding a pigment that selectively absorbs light near 470 nm and near 600 nm to a pressure-sensitive adhesive in order to improve the brightness and visibility of an organic EL image display device.

[0005] In these techniques, a pigment or a UV absorber is mainly added to a pressure-sensitive adhesive, but since the pressure-sensitive adhesive layer is thin, it is difficult to uniformly add a compound for developing a function.

[0006] In addition, in Patent Document 3, it is recorded that in order to block ultraviolet rays and a part of visible light rays from the outside, a variety of pigment compounds can also be added to any layer of the functional layer. Furthermore, in Patent Document 4, it is recorded that an indole compound is contained in a tackifier, etc., and in Patent Document 5, it is recorded that a pigment compound having a specific structure of a cyano group and an ester group is added to a resin or a functional layer, but there is a problem that the light resistance of any pigment compound is insufficient.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-165941

[0010] Patent Document 2: Japanese Patent No. 5599740

[0011] Patent Document 3: Japanese Patent Application Publication No. 2017-198991

[0012] Patent Document 4: International Publication No. 2017 / 15996

[0013] Patent Document 5: Japanese Patent Application Publication No. 2018-200463 Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present invention has been completed in view of the above-mentioned problems and circumstances, and aims to provide an optical film which has high transparency and prevents light leakage when applied to an image display device, and has excellent light resistance and durability under harsh environmental conditions, a polarizing plate having the optical film, and an organic electroluminescent image display device.

[0016] Means for solving problems

[0017] In order to solve the above-mentioned problems, the inventors have studied the causes of the above-mentioned problems and found that an optical film containing a thermoplastic resin and a compound with a specific structure can have high transparency when used in an image display device, prevent light leakage, and have excellent light resistance and durability under harsh environmental conditions.

[0018] That is, the above-mentioned problems according to the present invention are solved by the following means.

[0019] 1. An optical film comprising a thermoplastic resin, characterized in that the film comprises a compound having a structure represented by the following general formula (1).

[0020] [Chemistry 1]

[0021] General formula (1)

[0022]

[0023] (In the formula, Z represents a heteroaryl group having two or more heteroatoms, which may have a substituent.)

[0024] 2. The optical film according to item 1, wherein the Z is any group represented by the following structural formula.

[0025] [Chemistry 2]

[0026]

[0027] (The group represented by the above structural formula may further have a substituent. In addition, R represents a substituent.)

[0028] 3. The optical film according to item 2, characterized in that, further, the above-mentioned Z is any group represented by the following structural formula.

[0029] [Chemistry 3]

[0030]

[0031] (The group represented by the above structural formula may further have a substituent. In addition, R represents a substituent.)

[0032] 4. The optical film according to any one of items 1 to 3, wherein the energy level of the highest occupied orbital of the compound having a structure represented by the general formula (1) is -5.85 eV or less.

[0033] 5. The optical film according to any one of items 1 to 4, wherein the thermoplastic resin is a cyclic olefin resin or an acrylic resin.

[0034] 6. The optical film according to item 5, wherein the cyclic olefin-based resin has a polar group.

[0035] 7. The optical film according to any one of items 1 to 6, wherein the compound having a structure represented by the general formula (1) is contained in an amount within a range of 0.01 to 20% by mass based on the thermoplastic resin.

[0036] 8. The optical film according to any one of items 1 to 7, further comprising a functional layer.

[0037] 9. The optical film according to item 8, wherein the functional layer contains the compound having a structure represented by the general formula (1).

[0038] 10. The optical film according to any one of items 1 to 9, wherein the optical film is a λ / 4 retardation film.

[0039] 11. A polarizing plate comprising the optical film according to any one of items 1 to 10.

[0040] 12. An organic electroluminescent image display device, comprising the optical film according to any one of items 1 to 10 or the polarizing plate according to item 11.

[0041] Effects of the Invention

[0042] The above means of the present invention can provide an optical film which has high transparency and prevents light leakage when applied to an image display device, and has excellent light resistance and durability under severe environmental conditions, a polarizing plate having the optical film, and an organic electroluminescent image display device.

[0043] Although the manifestation mechanism and action mechanism of the effect of the present invention are not clearly understood, they are presumed as follows.

[0044] As the λ / 4 retardation film, a cyclic olefin-based resin film may be used from the viewpoint of low hygroscopicity and good dimensional stability.

[0045] However, in order to show a flat wavelength dispersion characteristic, when the cyclic olefin resin film is used as a λ / 4 phase difference film for a circular polarizer in an organic electroluminescent (hereinafter also referred to as "organic EL") image display device, reflected light is likely to leak in a specific wavelength region (region on the short wavelength side). If such leakage of reflected light is significant, the color tone of the reflected light is likely to be reduced.

[0046] In order to suppress the reduction of the hue caused by reflected light as mentioned above, the inventors etc. have studied and added the pigment compound of the light absorbing this wavelength region into the film. The organic EL image display device is used under the environment of high temperature and high humidity, so it is required to suppress the deterioration of the organic EL element caused by external light. In addition, because the pigment compound also deteriorates because of the incident light, the light resistance of the compound itself is also required.

[0047] Therefore, in order to solve such problems, it is considered that if a dye compound having a specific structure is used, light degradation can be suppressed, and further, if it is combined with a specific thermoplastic resin, a λ / 4 retardation film with improved overall durability can be produced.

[0048] As a result of the study, it was found that if a structure having a dicyano group is used as the pigment compound of the above-mentioned specific structure, the cyano group can reduce the energy level of the highest occupied molecular orbital (HOMO), that is, reduce the oxidation potential, thereby inhibiting photooxidation, and thus having the effect of improving the light resistance of the pigment compound. It was also found that if a resin type is selected in which the energy level of the highest occupied molecular orbital (HOMO) of the pigment compound and the energy level of the thermoplastic resin are unlikely to interact, the deterioration of light resistance and durability can be further inhibited. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a cross-sectional view showing the structure of the polarizing plate 100 .

[0050] Figure 2 is an exploded cross-sectional view of the organic EL image display device 200 . DETAILED DESCRIPTION

[0051] The optical film of the present invention is an optical film containing a thermoplastic resin, characterized in that it contains a compound having a structure represented by the above general formula (1). This feature is a common or corresponding technical feature of the following embodiments.

[0052] As an embodiment of the present invention, from the viewpoint of demonstrating the effects of the present invention and from the viewpoint of obtaining an optical film having an excellent balance between light leakage prevention and light resistance, it is preferred that Z in the structure represented by the above general formula (1) is any group in the structure represented by claim 2 or claim 3.

[0053] Furthermore, from the viewpoint of obtaining an optical film having excellent durability, the energy level of the highest occupied orbital of the compound having a structure represented by the general formula (1) is preferably -5.85 eV or less.

[0054] Furthermore, from the viewpoint of obtaining an optical film that prevents light leakage and has excellent light resistance and durability, the thermoplastic resin is preferably a cyclic olefin resin or an acrylic resin. In particular, when the cyclic olefin resin has a polar group, the energy level of the highest occupied orbital of the pigment and the energy level of the resin are unlikely to interact with each other, thereby suppressing the deterioration of light resistance and durability.

[0055] In the present invention, the compound having the structure represented by the general formula (1) is preferably contained in an amount of 0.01 to 20% by mass relative to the thermoplastic resin. If the amount is less than 0.01% by mass, the effect of the present invention is small, and if the amount exceeds 20% by mass, precipitation (also called seepage) from the film is likely to occur under high temperature and high humidity.

[0056] Furthermore, the optical film preferably has a functional layer, and the functional layer preferably contains the compound having the structure represented by the general formula (1). As the functional layer, a hard coating layer, an adhesive layer, a smooth layer or a light scattering layer can be cited, and from the viewpoint of imparting damage resistance to the optical film, a hard coating layer is preferred.

[0057] The optical film of the present invention is preferably a λ / 4 retardation film, and by including it in a polarizing plate, a circularly polarizing plate for antireflection can be provided.

[0058] Furthermore, the organic electroluminescent image display device of the present invention is characterized by comprising the optical film or polarizing plate of the present invention.

[0059] The present invention and its constituent elements, as well as forms and modes for implementing the present invention are described in detail below. It should be noted that in the present application, "to" is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0060] 《Overview of the optical film of the present invention》

[0061] The optical film of the present invention is an optical film containing a thermoplastic resin, and is characterized in containing a compound having a structure represented by the following general formula (1).

[0062] According to the present invention, by using a compound having a structure represented by general formula (1), the energy level of the highest occupied molecular orbital (HOMO) can be lowered. By lowering the energy level of HOMO, the oxidation potential can be lowered, and photooxidation can be suppressed. That is, the light resistance of the pigment compound can be improved.

[0063] Regarding the calculation of HOMO of the molecular orbital calculation of the compound having the structure represented by the general formula (1), as a calculation method, it can be calculated using a molecular orbital calculation software using B3LYP as a universal function and 6-31G(d) as a basis function. There is no particular limitation on the software, and the result can be obtained in the same manner using any one of them.

[0064] In the present invention, Gaussian09 (Revision C.01, MJ Frisch et al., Gaussian, Inc., 2010.) manufactured by Gaussian, Inc. of the United States was used as software for molecular orbital calculation.

[0065] The optical film of the present invention is preferably transparent, and "transparent" means a light transmittance of 80% or more when measured using a spectrophotometer (e.g., U-3300 manufactured by Hitachi HiTech Science) in accordance with JIS K 7375:2008 "Plastics - Methods for determining total light transmittance and total light reflectance".

[0066] Hereinafter, constituent elements of the present invention will be described in detail.

[0067] [1] Compounds having a structure represented by the general formula (1)

[0068] The compound having a structure represented by the general formula (1) according to the present invention (hereinafter also referred to as a "dye compound") has the following structure.

[0069] [Chemistry 4]

[0070] General formula (1)

[0071]

[0072] (In the formula, Z represents a heteroaryl group having two or more heteroatoms, which may have a substituent.)

[0073] Furthermore, in the formula, Z is an arbitrary group represented by the following structural formula, and may have a substituent. In the following structural formula, R represents a substituent.

[0074] [Chemistry 5]

[0075]

[0076] Among them, from the viewpoint of expressing the effects of the present invention, it is more preferable that the above-mentioned Z is any group represented by the following structural formula. In the following structural formula, R represents a substituent.

[0077] [Chemistry 6]

[0078]

[0079] The above R represents a substituent, and examples thereof include a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom, etc.), an alkyl group (methyl, ethyl, n-propyl, isopropyl, tert-butyl, n-octyl, 2-ethylhexyl, etc.), a cycloalkyl group (cyclohexyl, cyclopentyl, 4-n-dodecylcyclohexyl, etc.), an alkenyl group (vinyl, allyl, etc.), a cycloalkenyl group (2-cyclopenten-1-yl, 2-cyclohexen-1-yl, etc.), an alkynyl group (ethynyl, propargyl, etc.), an aromatic hydrocarbon ring group (phenyl, p-tolyl, naphthyl, etc.), an aromatic heterocyclic group (2-pyrrolyl, 2-furyl, 2-thienyl, pyrrolyl, imidazolyl, oxazolyl, thiazolyl, benzimidazolyl , benzoxazolyl, 2-benzothiazolyl, pyrazolone, pyridyl, pyridone, 2-pyrimidinyl, triazine, pyrazolyl, 1,2,3-triazolyl, 1,2,4-triazolyl, oxazolyl, isoxazolyl, 1,2,4-oxadiazolyl, 1,3,4-oxadiazolyl, thiazolyl, isothiazolyl, 1,2,4-thiadiazolyl, 1,3,4-thiadiazolyl, etc.), cyano, hydroxyl, nitro, carboxyl, alkoxy (methoxy, ethoxy, isopropoxy, tert-butoxy, n-octyloxy, 2-methoxyethoxy, etc.), aryloxy (phenoxy, 2-methylphenoxy, 4-tert-butylphenoxy, 3-nitrophenoxy, 2 -tetradecanoylaminophenoxy, etc.), acyloxy (formyloxy, acetyloxy, pivaloyloxy, stearoyloxy, benzoyloxy, p-methoxyphenylcarbonyloxy, etc.), amino (amino, methylamino, dimethylamino, anilino, N-methyl-anilino, diphenylamino, etc.), acylamino (formylamino, acetylamino, pivaloylamino, lauroylamino, benzoylamino, etc.), alkyl and arylsulfonylamino (methylsulfonylamino, butylsulfonylamino, phenylsulfonylamino, 2,3,5-trichlorophenylsulfonylamino, p-methylphenylsulfonylamino, etc.), mercapto, alkylthio (methylthio, ethylthio The invention also includes various groups such as thio (amino, anthio, hexadecylthio, etc.), arylthio (phenylthio, p-chlorophenylthio, m-methoxyphenylthio, etc.), sulfamoyl (N-ethylsulfamoyl, N-(3-dodecyloxypropyl)sulfamoyl, N,N-dimethylsulfamoyl, N-acetylsulfamoyl, N-benzoylsulfamoyl, N-(N′-phenylcarbamoyl)sulfamoyl, etc.), sulfo, acyl (acetyl, pivaloylbenzoyl, etc.), carbamoyl (carbamoyl, N-methylcarbamoyl, N,N-dimethylcarbamoyl, N,N-di-n-octylcarbamoyl, N-(methylsulfonyl)carbamoyl, etc.).

[0080] Hereinafter, the dye compound having a structure represented by the general formula (1) according to the present invention will be exemplified, but the present invention is not limited thereto.

[0081] [Chemistry 7]

[0082]

[0083] [Chemistry 8]

[0084]

[0085] [Chemistry 9]

[0086]

[0087] [Chemistry 10]

[0088]

[0089] The molecular weight of the pigment compound is not particularly limited, but is preferably not too large in order to easily enter between molecules of the cyclic olefin resin and the acrylic resin, and is preferably 100 to 1000. The molecular weight of the pigment compound can be determined by, for example, using an NMR (Nuclear Magnetic Resonance) device to determine the chemical structure and calculate the formula weight from the chemical structure.

[0090] The maximum absorption wavelength of the pigment compound is preferably in the range of 370 to 460 nm, more preferably in the range of 400 to 440 nm. If the maximum absorption wavelength of the pigment compound is within the above range, the optical film is easy to absorb the light of the wavelength region appropriately, so for example, when the optical film is used as a λ / 4 phase difference film in an organic EL image display device, the leakage of reflected light in the wavelength region can be further suppressed. The maximum absorption wavelength of the pigment compound can be obtained by measuring the absorption spectrum of the pigment compound in dichloromethane using an ultraviolet visible spectrophotometer UV-2450 manufactured by Shimadzu Corporation.

[0091] The pigment compound may be obtained by synthesis or a commercial product may be used. For example, the synthesis of the exemplary pigment compound 12 can be performed by the following scheme.

[0092] [Chemistry 11]

[0093] Exemplary pigment compound 12

[0094]

[0095] In a 100mL three-necked flask, 1.5g of compound (12-1) and 0.697g of malononitrile were measured, 40mL of toluene was added and dissolved. Then 0.817g of morpholine was added dropwise, the temperature was raised, and heated to reflux for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, 10mL of methanol was added, and the mixture was stirred in a suspended state. The precipitate was filtered and dried to obtain 1.89g (yield 96%) of powder of the illustrative pigment compound 12. The structure was confirmed by NMR.

[0096] With regard to the content of the pigment compound, relative to the cyclic olefin resin, it is preferably in the range of 0.01 to 20% by mass. If the content of the pigment compound is more than 0.01% by mass, the light of the specific wavelength region is appropriately absorbed, for example, the leakage of the reflected light in the organic EL image display device can be suppressed and the effect of improving light resistance can be obtained. If the content of the pigment compound is below 20% by mass, it is not only difficult to produce oozing out, but also the absorption of the light of the specific wavelength region of the optical film will not be excessively improved, so the reduction of brightness can also be suppressed. With regard to the content of the pigment compound, from the same viewpoint, relative to the cyclic olefin resin, it is more preferably in the range of 0.015 to 10% by mass.

[0097] 〔2〕Thermoplastic resin

[0098] As the thermoplastic resin material of the present invention, there is no limitation as long as it can be treated as a film after film making. For example, as the thermoplastic resin used for polarizer purposes, cellulose ester resins such as triacetyl cellulose (TAC), cellulose acetate propionate (CAP), diacetyl cellulose (DAC), cycloolefin polymers (hereinafter also referred to as COP, cycloolefin resins) and other cyclic olefin resins, polypropylene resins such as polypropylene (PP), acrylic resins such as polymethyl methacrylate (PMMA), and polyester resins such as polyethylene terephthalate (PET) can be applied.

[0099] Among them, cyclic olefin resins and acrylic resins are preferred from the viewpoint of optical properties including phase difference and physical properties such as durability.

[0100] 〔2.1〕Cycloolefin resin

[0101] The cycloolefin-based resin contained in the optical film of the present invention is preferably a polymer of a cycloolefin monomer or a copolymer of a cycloolefin monomer and another copolymerizable monomer.

[0102] The cycloolefin monomer is preferably a cycloolefin monomer having a norbornene skeleton, and more preferably a cycloolefin monomer having a structure represented by the following general formula (A-1) or (A-2).

[0103] [Chemistry 12]

[0104] General formula (A-1)

[0105]

[0106] In the general formula (A-1), R 1 ~R 4 Each independently represents a hydrogen atom, a hydrocarbon group having 1 to 30 carbon atoms, or a polar group. p represents an integer of 0 to 2. 1 ~R 4All different at the same time represent hydrogen atoms, R 1 and R 2 Not at the same time representing hydrogen atoms, R 3 and R 4 It does not represent hydrogen atoms at the same time.

[0107] In the general formula (A-1), R 1 ~R 4 The hydrocarbon group having 1 to 30 carbon atoms represented by is preferably a hydrocarbon group having 1 to 10 carbon atoms, and more preferably a hydrocarbon group having 1 to 5 carbon atoms. The hydrocarbon group having 1 to 30 carbon atoms may further have a linking group containing a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom or a silicon atom. Examples of such linking groups include bivalent polar groups such as a carbonyl group, an imino group, an ether bond, a silyl ether bond, and a thioether bond. Examples of hydrocarbon groups having 1 to 30 carbon atoms include methyl, ethyl, propyl, and butyl.

[0108] In the general formula (A-1), R 1 ~R 4 Examples of polar groups represented by include carboxyl, hydroxyl, alkoxy, alkoxycarbonyl, aryloxycarbonyl, amino, amide and cyano. Among them, carboxyl, hydroxyl, alkoxycarbonyl and aryloxycarbonyl are preferred, and alkoxycarbonyl and aryloxycarbonyl are preferred from the viewpoint of ensuring solubility during film formation of the solution.

[0109] From the viewpoint of improving the heat resistance of the optical film, p in the general formula (A-1) is preferably 1 or 2. This is because when p is 1 or 2, the volume of the obtained polymer becomes large and the glass transition temperature tends to increase.

[0110] [Chemistry 13]

[0111] General formula (A-2)

[0112]

[0113] In the general formula (A-2), R 5 R represents a hydrogen atom, a hydrocarbon group having 1 to 5 carbon atoms, or an alkylsilyl group having an alkyl group having 1 to 5 carbon atoms. 6 represents a carboxyl group, a hydroxyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amide group, a cyano group or a halogen atom (a fluorine atom, a chlorine atom, a bromine atom or an iodine atom). p represents an integer of 0 to 2.

[0114] R in the general formula (A-2) 5 It preferably represents a hydrocarbon group having 1 to 5 carbon atoms, and more preferably represents a hydrocarbon group having 1 to 3 carbon atoms.

[0115] R in the general formula (A-2) 6Preferably, it represents a carboxyl group, a hydroxyl group, an alkoxycarbonyl group, and an aryloxycarbonyl group. From the viewpoint of ensuring solubility during film formation from a solution, an alkoxycarbonyl group and an aryloxycarbonyl group are more preferred.

[0116] From the viewpoint of improving the heat resistance of the optical film, p in the general formula (A-2) preferably represents 1 or 2. This is because when p represents 1 or 2, the volume of the obtained polymer becomes large and the glass transition temperature tends to increase.

[0117] From the perspective of improving solubility in organic solvents, cycloolefin monomers having a structure represented by general formula (A-2) are preferred. Generally, organic compounds have reduced crystallinity by destroying symmetry, thereby improving solubility in organic solvents. 5 and R 6 Since the ring-constituting carbon atoms are substituted only on one side of the molecular symmetry axis, the molecular symmetry is low, that is, the cycloolefin monomer having the structure represented by general formula (A-2) has high solubility and is therefore suitable for producing an optical film by a solution casting method.

[0118] The content ratio of the cycloolefin monomer having a structure represented by the general formula (A-2) in the polymer of the cycloolefin monomer may be, for example, 70 mol% or more, preferably 80 mol% or more, and more preferably 100 mol% relative to the total of all cycloolefin monomers constituting the cycloolefin resin. If the cycloolefin monomer having a structure represented by the general formula (A-2) is contained in a certain amount or more, the orientation of the resin is improved, and thus the phase difference (retardation) value is likely to increase.

[0119] Hereinafter, specific examples of the cycloolefin monomer having a structure represented by the general formula (A-1) are shown in Exemplary Compounds 1 to 14, and specific examples of the cycloolefin monomer having a structure represented by the general formula (A-2) are shown in Exemplary Compounds 15 to 34.

[0120] [Chemistry 14]

[0121]

[0122] Examples of the copolymerizable monomer copolymerizable with the cycloolefin monomer include a copolymerizable monomer capable of ring-opening copolymerization with the cycloolefin monomer and a copolymerizable monomer capable of addition copolymerization with the cycloolefin monomer.

[0123] Examples of the copolymerizable monomers capable of ring-opening copolymerization include cycloolefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, and dicyclopentadiene.

[0124] Examples of copolymerizable monomers capable of addition copolymerization include compounds containing unsaturated double bonds, vinyl cyclic hydrocarbon monomers, and (meth)acrylates. Examples of compounds containing unsaturated double bonds include olefin compounds having 2 to 12 carbon atoms (preferably 2 to 8), examples of which include ethylene, propylene, and butene. Examples of vinyl cyclic hydrocarbon monomers include vinyl cyclopentene monomers such as 4-vinylcyclopentene and 2-methyl-4-isopropenylcyclopentene. Examples of (meth)acrylates include alkyl (meth)acrylates having 1 to 20 carbon atoms such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.

[0125] The content ratio of the cycloolefin monomer in the copolymer of the cycloolefin monomer and the copolymerizable monomer may be, for example, 20 to 80 mol %, preferably 30 to 70 mol % based on the total of all monomers constituting the copolymer.

[0126] As described above, the cycloolefin resin is a polymer obtained by polymerizing or copolymerizing a cycloolefin monomer having a norbornene skeleton, preferably a cycloolefin monomer having a structure represented by the general formula (A-1) or (A-2), and examples thereof include the following.

[0127] (1) Ring-opening polymers of cycloolefin monomers

[0128] (2) Ring-opening copolymers of cycloolefin monomers and copolymerizable monomers capable of ring-opening copolymerization therewith

[0129] (3) Hydrogenated product of the ring-opening (co)polymer of (1) or (2) above

[0130] (4) Cyclizing the ring-opening (co)polymer of (1) or (2) by Friedel-Crafts reaction, and then hydrogenating the (co)polymer

[0131] (5) Saturated copolymers of cycloolefin monomers and compounds containing unsaturated double bonds

[0132] (6) Addition copolymers of cycloolefin monomers and vinyl cyclic hydrocarbon monomers and their hydrogenated products

[0133] (7) Alternating copolymers of cycloolefin monomers and (meth)acrylates

[0134] The polymers of (1) to (7) above can be obtained by known methods such as the methods described in Japanese Patent Application Laid-Open No. 2008-107534 and Japanese Patent Application Laid-Open No. 2005-227606. For example, the catalyst and solvent used in the ring-opening copolymerization of (2) above can be the catalysts and solvents described in paragraphs 0019 to 0024 of Japanese Patent Application Laid-Open No. 2008-107534. The catalyst used in the hydrogenation of (3) and (6) above can be the catalysts described in paragraphs 0025 to 0028 of Japanese Patent Application Laid-Open No. 2008-107534. The acidic compound used in the Friedel-Crafts reaction of (4) above can be the compound described in paragraph 0029 of Japanese Patent Application Laid-Open No. 2008-107534. The catalyst used in the addition polymerization of (5) to (7) can be, for example, the catalysts described in paragraphs 0058 to 0063 of JP-A-2005-227606. The alternating copolymerization reaction of (7) can be carried out by the method described in paragraphs 0071 and 0072 of JP-A-2005-227606.

[0135] Among them, the polymers of (1) to (3) and (5) are preferred, and the polymers of (3) and (5) are more preferred. That is, the cycloolefin resin preferably contains at least one of the structural unit represented by the following general formula (B-1) and the structural unit represented by the following general formula (B-2), and more preferably contains only the structural unit represented by the general formula (B-2), or contains both the structural unit represented by the general formula (B-1) and the structural unit represented by the general formula (B-2). The structural unit represented by the general formula (B-1) is a structural unit derived from the cycloolefin monomer represented by the general formula (A-1), and the structural unit represented by the general formula (B-2) is a structural unit derived from the cycloolefin monomer represented by the general formula (A-2).

[0136] [Chemistry 15]

[0137] General formula (B-1)

[0138]

[0139] In the general formula (B-1), X represents -CH=CH- or -CH2CH2-. 1 ~R 4 and p are respectively the same as R 1 ~R 4 Synonymous with p.

[0140] [Chemistry 16]

[0141] General formula (B-2)

[0142]

[0143] In the general formula (B-2), X represents -CH=CH- or -CH2CH2-. 5 ~R 6 and p are respectively the same as R 5 ~R 6 Synonymous with p.

[0144] The cycloolefin resin of the present invention may be a commercially available product. Examples of commercially available cycloolefin resins include Arton G (eg, G7810), Arton F, Arton R (eg, R4500, R4900, R5000, etc.), and Arton RX manufactured by JSR Corporation.

[0145] The intrinsic viscosity of the cycloolefin resin (η) inh is preferably 0.2 to 5 cm 3 / g, more preferably 0.3 to 3 cm 3 / g, more preferably 0.4 to 1.5 cm 3 / g range.

[0146] The number average molecular weight (Mn) of the cycloolefin-based resin is preferably in the range of 8,000 to 100,000, more preferably in the range of 10,000 to 80,000, and even more preferably in the range of 12,000 to 50,000.

[0147] The weight average molecular weight (Mw) of the cycloolefin-based resin is preferably in the range of 20,000 to 300,000, more preferably in the range of 30,000 to 250,000, and even more preferably in the range of 40,000 to 200,000.

[0148] The number average molecular weight and weight average molecular weight of the cycloolefin resin can be measured in terms of polystyrene by gel permeation chromatography (GPC).

[0149] <Gel Permeation Chromatography>

[0150] Solvent: dichloromethane

[0151] Column: Shodex K806, K805, K803G (connect three made by Showa Denko K.K.)

[0152] Column temperature: 25°C

[0153] Sample concentration: 0.1 mass%

[0154] Detector: RI Model 504 (manufactured by GL Science)

[0155] Pump: L6000 (manufactured by Hitachi, Ltd.)

[0156] Flow rate: 1.0mL / min

[0157] Calibration curve: A calibration curve obtained by using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) in the range of Mw=500 to 2800000 is used. The 13 samples are preferably used at substantially equal intervals.

[0158] When the intrinsic viscosity [η]inh, the number average molecular weight and the weight average molecular weight are within the above ranges, the heat resistance, water resistance, chemical resistance, mechanical properties and film molding processability of the cycloolefin resin become good.

[0159] The glass transition temperature (Tg) of the cycloolefin resin is usually 110°C or higher, preferably in the range of 110 to 350°C, more preferably in the range of 120 to 250°C, and further preferably in the range of 120 to 220°C. When Tg is 110°C or higher, deformation under high temperature conditions is easily suppressed. On the other hand, when Tg is 350°C or lower, molding processing becomes easy and degradation of the resin caused by heat during molding processing is also easily suppressed.

[0160] The content of the cycloolefin-based resin is preferably 70% by mass or more, more preferably 80% by mass or more, based on the film.

[0161] 〔2.2〕Acrylic resin

[0162] The acrylic resin according to the present invention is a polymer of acrylic acid ester or methacrylic acid ester, and also includes a copolymer with other monomers.

[0163] Therefore, the acrylic resin according to the present invention also includes methacrylic resin. The resin is not particularly limited, but preferably contains 50 to 99% by mass of methyl methacrylate units and 1 to 50% by mass of other monomer units copolymerizable therewith.

[0164] Other units constituting the acrylic resin formed by copolymerization include alkyl methacrylates having an alkyl group with 2 to 18 carbon atoms, alkyl acrylates having an alkyl group with 1 to 18 carbon atoms, hydroxyalkyl acrylates such as isobornyl methacrylate and 2-hydroxyethyl acrylate, α,β-unsaturated acids such as acrylic acid and methacrylic acid, acrylamides such as acryloylmorpholine and N-hydroxyphenylmethacrylamide, N-vinylpyrrolidone, dicarboxylic acids containing unsaturated groups such as maleic acid, fumaric acid and itaconic acid, aromatic vinyl compounds such as styrene and α-methylstyrene, α,β-unsaturated nitriles such as acrylonitrile and methacrylonitrile, maleic anhydride, maleimide, N-substituted maleimide, glutarimide, glutaric anhydride, and the like.

[0165] Examples of copolymerizable monomers that form units excluding glutarimide and glutaric anhydride from the above units include monomers corresponding to the above units, namely, alkyl methacrylates having 2 to 18 carbon atoms in the alkyl group, alkyl acrylates having 1 to 18 carbon atoms in the alkyl group, hydroxyalkyl acrylates such as isobornyl methacrylate and 2-hydroxyethyl acrylate, α,β-unsaturated acids such as acrylic acid and methacrylic acid, acrylamides such as acryloylmorpholine and N-hydroxyphenylmethacrylamide, N-vinylpyrrolidone, dicarboxylic acids containing unsaturated groups such as maleic acid, fumaric acid and itaconic acid, aromatic vinyl compounds such as styrene and α-methylstyrene, α,β-unsaturated nitriles such as acrylonitrile and methacrylonitrile, maleic anhydride, maleimide, and N-substituted maleimide.

[0166] The glutarimide unit can be formed, for example, by reacting a primary amine (imidating agent) with an intermediate polymer having a (meth)acrylate unit to imidize the intermediate polymer (see JP-A No. 2011-26563).

[0167] The glutaric anhydride unit can be formed, for example, by heating an intermediate polymer having a (meth)acrylic acid ester unit (see Japanese Patent No. 4961164).

[0168] In the acrylic resin according to the present invention, among the above structural units, it is particularly preferred that isobornyl methacrylate, acryloylmorpholine, N-hydroxyphenylmethacrylamide, N-vinylpyrrolidone, styrene, hydroxyethyl methacrylate, maleic anhydride, maleimide, N-substituted maleimide, glutaric anhydride or glutarimide be contained from the viewpoint of mechanical strength.

[0169] From the viewpoint of controlling dimensional changes due to changes in the temperature and humidity atmosphere of the environment, the peelability from the metal support during film production, the drying property of organic solvents, the heat resistance and the improvement of mechanical strength, the weight average molecular weight (Mw) of the acrylic resin involved in the present invention is preferably in the range of 50,000 to 1,000,000, more preferably in the range of 100,000 to 1,000,000, and particularly preferably in the range of 200,000 to 800,000.

[0170] When it is 50,000 or more, the heat resistance and mechanical strength are excellent, and when it is 1,000,000 or less, the peeling property from the metal support and the drying property of the organic solvent are excellent.

[0171] The method for producing the acrylic resin of the present invention is not particularly limited, and any of the known methods such as suspension polymerization, emulsion polymerization, bulk polymerization or solution polymerization can be used. Here, as the polymerization initiator, a conventional peroxide-based and azo-based polymerization initiator can be used, and a redox-based polymerization initiator can also be used. The polymerization temperature can be implemented in the range of 30 to 100° C. in suspension or emulsion polymerization, and in the range of 80 to 160° C. in bulk or solution polymerization. In order to control the reduced viscosity of the obtained copolymer, an alkyl mercaptan or the like can also be used as a chain transfer agent for polymerization.

[0172] From the viewpoint of maintaining the mechanical strength of the film, the glass transition temperature Tg of the acrylic resin is preferably within a range of 80 to 120°C.

[0173] As the acrylic resin of the present invention, commercial products can also be used. For example, Delupet 60N, 80N, 980N, SR8200 (manufactured by Asahi Kasei Chemicals), Diyanal BR52, BR80, BR83, BR85, BR88, EMB-143, EMB-159, EMB-160, EMB-161, EMB-218, EMB-229, EMB-270, EMB-273 (manufactured by Mitsubishi Rayon), KT75, TX400S, IPX012 (manufactured by Denki Kagaku Kogyo), etc. Two or more acrylic resins can also be used in combination.

[0174] The acrylic resin of the present invention preferably contains an additive, and as an example of the additive, it is preferred to contain acrylic particles (rubber elastic particles) described in International Publication No. 2010 / 001668 in order to improve the mechanical strength of the film and adjust the dimensional change rate. Examples of commercially available products of such multilayer acrylic granular composites include "METABLEN W-341" manufactured by Mitsubishi Rayon Co., Ltd., "KaneAce" manufactured by Kaneka Co., Ltd., "Paraloid" manufactured by KUREHA CORPORATION, "Acryloid" manufactured by Rohm and Haas Co., Ltd., "Stafyloid" manufactured by Ika Co., Ltd., Chemisno MR-2G, MS-300X (the above are manufactured by Soken Chemical (Strain)) and "Parapet SA" manufactured by Kuraray Co., Ltd., etc., which can be used alone or in combination of two or more.

[0175] The volume average particle size of the acrylic particles is 0.35 μm or less, preferably in the range of 0.01 to 0.35 μm, and more preferably in the range of 0.05 to 0.30 μm. If the particle size is above a certain value, the film can be easily stretched under heating, and if the particle size is below a certain value, the transparency of the obtained film is less likely to be impaired.

[0176] From the viewpoint of flexibility, the bending elastic modulus (JIS K7171) of the optical film of the present invention is preferably below 1.5 GPa. The bending elastic modulus is more preferably below 1.3 GPa, and further preferably below 1.2 GPa. The bending elastic modulus varies according to the type and amount of the acrylic resin and rubber elastic particles in the film, for example, the more the content of the rubber elastic particles, the smaller the general bending elastic modulus. In addition, as an acrylic resin, when a copolymer of an alkyl methacrylate and an alkyl acrylate is used, the bending elastic modulus usually decreases compared to a homopolymer using an alkyl methacrylate.

[0177] 〔3〕Other ingredients

[0178] The optical film of the present invention may further contain other components other than the above within the scope that does not impair the effect of the present invention. Examples of other components include matting agents, ultraviolet absorbers, phase difference adjusters (phase difference increasing agents, phase difference reducing agents), plasticizers, antioxidants, light stabilizers, antistatic agents, release agents, and tackifiers. Among them, the optical film preferably contains a matting agent from the viewpoint of imparting unevenness to the surface of the optical film and imparting appropriate slip properties.

[0179] (Matting agent)

[0180] The matting agent is a particle. The particle can be an inorganic particle or a resin particle. Examples of inorganic particles include particles of inorganic compounds such as silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate and calcium phosphate. Among them, the inorganic particles are preferably silicon dioxide particles from the viewpoint of being difficult to increase the haze of the optical film and being able to effectively reduce the friction coefficient.

[0181] Examples of silica fine particles include Aestrotech 200V, Aestron R972V, and Aestro R812 (the above are manufactured by Nippon Aestro Co., Ltd.).

[0182] Examples of resin particles include particles of silicone resin, fluororesin, acrylic resin, etc. Among them, silicone resin particles are preferred, and resin particles having a three-dimensional network structure are particularly preferred. Examples of resin particles include Tospar 103, 105, 108, 120, 145, 3120, and 240 (all manufactured by Toshiba Silicone Co., Ltd.).

[0183] The average particle size of primary particles of the fine particles is preferably in the range of 0.005 to 0.4 μm, more preferably in the range of 0.01 to 0.3 μm. These fine particles may be contained as secondary agglomerates having a particle size in the range of 0.05 to 0.3 μm.

[0184] The content of the fine particles is preferably in the range of 0.01 to 3.0% by mass, more preferably in the range of 0.01 to 2.0% by mass, relative to the optical film. The dynamic friction coefficient of the surface of the optical film is preferably in the range of 0.2 to 1.0.

[0185] [4] Method for producing optical film

[0186] 〔4.1〕Physical properties of optical films

[0187] (Phase difference Ro)

[0188] For example, in view of using the optical film as a λ / 4 retardation film, the retardation Ro in the in-plane direction measured at a measurement wavelength of 550 nm and an environment of 23°C and 55% RH is preferably in the range of 100 to 170 nm, more preferably 130 to 150 nm.

[0189] Ro is defined by the following formula.

[0190] Formula (1): Ro=(n x -n y )×d

[0191] (In formula (1), n x It represents the refractive index in the slow axis direction (the direction with the maximum refractive index) of the film. y represents the refractive index of the film in a direction perpendicular to the in-plane slow axis, and d represents the thickness of the film (nm).

[0192] The in-plane slow axis of the optical film can be confirmed by an automatic birefringence meter AxoScan (Axo Scan Mueller Matrix Polarimeter: manufactured by Axometrics). When the optical film is used as a λ / 4 phase difference film, the angle of the in-plane slow axis of the optical film relative to the width direction of the optical film is preferably in the range of 40 to 50°, and more preferably in the range of 43 to 47°.

[0193] Ro can be measured by the following method.

[0194] 1) The optical film was humidified for 24 hours in an environment of 23° C. and 55% RH. The average refractive index of the film was measured using an Abbe refractometer, and the thickness d was measured using a commercially available micrometer.

[0195] 2) The retardation Ro of the humidity-controlled film at a measurement wavelength of 550 nm was measured in an environment of 23° C. and 55% RH using an automatic birefringence meter AxoScan (Axo Scan Mueller Matrix Polarimeter: manufactured by Axometrics).

[0196] The phase difference Ro of the optical film can be adjusted by, for example, the monomer composition of the cycloolefin-based resin and the stretching conditions.

[0197] (Residual solvent amount)

[0198] The optical film is preferably formed by a solution casting method, and therefore may further contain a residual solvent. The amount of the residual solvent is preferably 700 ppm or less, more preferably in the range of 30 to 700 ppm relative to the optical film. The content of the residual solvent can be adjusted by the drying conditions of the dope cast on the support in the manufacturing process of the optical film.

[0199] The amount of residual solvent in an optical film can be measured by headspace gas chromatography. In headspace gas chromatography, a sample is sealed in a container, heated, and the gas in the container is quickly injected into a gas chromatograph while the container is full of volatile components. Mass analysis is performed to identify the compounds while quantifying the volatile components. In the headspace method, all peaks of volatile components can be observed by gas chromatography, and by using an analysis method that utilizes electromagnetic interaction, volatile substances, monomers, etc. can be quantified at the same time with high precision.

[0200] (thickness)

[0201] The thickness of the optical film of the present invention is not particularly limited, but is preferably in the range of 10 to 80 μm, and more preferably in the range of 10 to 60 μm.

[0202] 〔4.2〕Method for manufacturing optical film

[0203] The optical film of the present invention can be manufactured through the following steps: 1) preparing a dope containing the above-mentioned cycloolefin resin or acrylic resin, the above-mentioned pigment compound and a solvent; 2) casting the obtained dope on a support, drying and peeling it off to obtain a cast film; and 3) stretching the obtained cast film. In addition, the optical film of the present invention can be manufactured through 4) drying the stretched cast film, 5) cutting both ends of the obtained optical film and embossing it, and 6) winding it.

[0204] Regarding the process of 1) (dope preparation process)

[0205] The cycloolefin resin or acrylic resin and the pigment compound are dissolved or dispersed in a solvent to prepare a dope.

[0206] The solvent used for the glue contains at least an organic solvent (good solvent) capable of dissolving the cycloolefin resin. Examples of the good solvent include chlorine-based organic solvents such as dichloromethane and non-chlorine-based organic solvents such as methyl acetate, ethyl acetate, acetone, and tetrahydrofuran. Among them, dichloromethane is preferred.

[0207] The solvent used for the glue may further contain a poor solvent. Examples of poor solvents include straight-chain or branched aliphatic alcohols having 1 to 4 carbon atoms. If the ratio of alcohol in the glue increases, the film-like material is easily gelled and easily peeled off from the metal support. As straight-chain or branched aliphatic alcohols having 1 to 4 carbon atoms, methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and tert-butanol can be cited. Among them, ethanol is preferred from the perspectives of the stability of the glue, relatively low boiling point, and good drying properties.

[0208] Regarding the step 2) (casting step)

[0209] The obtained dope is cast on a support. The dope can be cast by discharging from a casting die.

[0210] The solvent is evaporated until the dope cast on the support can be peeled off from the support by a peeling roller. Methods for evaporating the solvent include a method of blowing air to the cast dope, a method of transferring heat from the back of the support using liquid, and a method of transferring heat from the front and back using radiant heat.

[0211] Then, the cast film obtained by evaporating the solvent is peeled off with a peeling roll.

[0212] The residual solvent amount of the cast film on the support during peeling also depends on the drying conditions, the length of the support, etc., and can be, for example, in the range of 50 to 120 mass%. If peeling is performed in a state where the residual solvent amount is large, the cast film is too soft, the planarity is easily damaged during peeling, and wrinkles and longitudinal stripes caused by the peeling tension are easily generated. Therefore, considering these points, the residual solvent amount during peeling is determined. The residual solvent amount is defined by the following formula.

[0213] Residual solvent amount (mass %) = (mass of cast film before heating treatment - mass of cast film after heating treatment) / (mass of cast film after heating treatment) × 100

[0214] The heat treatment for measuring the residual solvent amount was performed at 115° C. for 1 hour.

[0215] Regarding the process 3) (stretching process)

[0216] The cast film obtained by peeling off from the support is stretched.

[0217] Stretching can be performed according to the required optical properties, preferably in one or more directions of the width direction (TD direction), the conveying direction (MD direction), and the oblique direction. For example, in the case of manufacturing an optical film that functions as a λ / 4 phase difference film, it is preferably stretched in the oblique direction.

[0218] The stretch ratio also depends on the required optical properties, and when used as a λ / 4 retardation film, for example, it is preferably in the range of 1.05 to 4.0 times, and more preferably in the range of 1.5 to 3.0 times.

[0219] The stretch ratio (times) is defined as the stretching direction size of the film after stretching / the stretching direction size of the film before stretching. In the case of biaxial stretching, it is preferable to set the stretch ratios in the TD direction and the MD direction as described above.

[0220] The stretching temperature (drying temperature during stretching) is the same as above. When the glass transition temperature of the cycloolefin resin is set to Tg, it is preferably in the range of (Tg+2) to (Tg+50)°C, and more preferably in the range of (Tg+5) to (Tg+30)°C. If the stretching temperature is (Tg+2)°C or more, the solvent is easily volatilized appropriately, so it is easy to adjust the stretching tension to an appropriate range. If it is (Tg+50) or less, the solvent will not volatilize excessively, so the stretchability is not easily impaired. The stretching temperature is the same as above, and it is preferably measured (a) The atmospheric temperature such as the temperature inside the stretching machine.

[0221] The amount of residual solvent in the film at the start of stretching is preferably about the same as the amount of residual solvent in the film at the time of peeling, for example, preferably in the range of 20 to 30 mass %, more preferably in the range of 25 to 30 mass %.

[0222] The stretching of the film in the TD direction (width direction) can be performed by, for example, using a clamp or a needle to fix the two ends of the film and expanding the interval between the clamp or the needle in the traveling direction (the tentering method). The stretching of the film in the MD direction can be performed by, for example, giving a peripheral speed difference to a plurality of rollers and using the peripheral speed difference of the rollers therebetween (the roller method). In particular, in order to improve the planarity and dimensional stability of the film, it is preferred to use a tentering method in which the two ends of the cast film are held and stretched by a clamp or the like. It is preferred to stretch the cast film in both the MD direction and the TD direction, thereby stretching it in a direction obliquely intersecting with respect to the MD direction and the TD direction (oblique stretching).

[0223] About the process of 4) (drying process)

[0224] The stretched cast film is further dried to obtain an optical film.

[0225] The casting film can be dried, for example, while conveying the casting film using a plurality of conveyor rollers (for example, a plurality of conveyor rollers arranged in a staggered shape when viewed from the side). The drying method is not particularly limited, and hot air, infrared rays, a heating roller or a microwave can be used. From the perspective of simplicity, hot air drying is preferred.

[0226] Regarding the process of 5) (cutting and embossing process)

[0227] The optical film is cut at both ends in the width direction. The cutting of both ends of the optical film can be performed by a cutter.

[0228] Next, embossing (knurling) is performed on both ends of the optical film in the width direction. The embossing process can be performed by pressing a heated embossing roller to both ends of the optical film. Fine concave and convex are formed on the surface of the embossing roller, and by pressing the embossing roller to both ends of the optical film, concave and convex are formed at both ends. By such embossing, winding deviation and adhesion (sticking of films to each other) in the subsequent winding process can be suppressed as much as possible.

[0229] Regarding the process of 6) (winding process)

[0230] Then, the obtained optical film is wound to obtain a roll.

[0231] That is, the optical film is wound around a winding core while being conveyed to form a roll. The winding method of the optical film can be any commonly used method using a winder, and there are methods for controlling tension such as a constant torque method, a constant tension method, a gradual tension method, and a program tension control method with constant internal stress.

[0232] The roll length of the optical film in the roll is preferably in the range of 1000 to 7200 m. The width of the optical film is preferably in the range of 1000 to 3000 mm.

[0233] 〔5〕Other functional layers

[0234] The optical film of the present invention preferably has a functional layer, and the functional layer preferably contains a compound having a structure represented by the general formula (1). As the functional layer, a hard coating layer, an antistatic layer, an antireflection layer, an easy-slip layer, an adhesive layer, an antiglare layer, a barrier layer, etc. can be listed. When assembled in an organic EL image display device, in order to improve the damage resistance, a hard coating layer is preferably provided.

[0235] 〔5.1〕Hard coating

[0236] From the perspective of excellent mechanical film strength (scratch resistance, pencil hardness), the hard coat used in the present invention preferably contains an active ray-cured resin. That is, it is a layer with a resin cured by irradiation with active rays (also called active energy rays) such as ultraviolet rays and electron beams and a crosslinking reaction as the main component. As an active ray-cured resin, it is preferred to use a component containing a monomer having an ethylenically unsaturated double bond, and to form an active ray-cured resin layer by curing it by irradiating active rays such as ultraviolet rays and electron beams. As an active ray-cured resin, ultraviolet curing resins, electron beam curing resins, etc. can be cited as representative resins, and in particular, from the perspective of excellent mechanical film strength (scratch resistance, pencil hardness), resins cured by ultraviolet irradiation are preferred. As an ultraviolet curing resin, for example, ultraviolet curing acrylate resins, ultraviolet curing urethane acrylate resins, ultraviolet curing polyester acrylate resins, ultraviolet curing epoxy acrylate resins, ultraviolet curing polyol acrylate resins, or ultraviolet curing epoxy resins are preferably used, among which ultraviolet curing acrylate resins are preferred.

[0237] Examples of commercially available products include the ADECAOPT MATER N series, SANDRAD H-601, RC-750, RC-700, RC-600, RC-500, RC-611, and RC-612 (all manufactured by Sanyo Chemical Industries, Ltd.), ARONIX M-6100, M-8030, M-8060, ARONIX M-215, ARONIX M-315, ARONIX M-313, and ARONIX M-327 (all manufactured by Toagosei Co., Ltd.), NK-ESTER A-TMM-3L, NK-ESTER AD-TMP, NK-ESTER ATM-35E, NK ESTER A-DOG, and NK ESTER A-IBD-2E, A-9300, A-9300-1CL (all manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), PE-3A (manufactured by Kyoeisha Chemical Industry Co., Ltd.), etc. The above active radiation curing resins may be used alone or in combination of two or more.

[0238] In addition, in order to promote the curing of the active radiation curing resin, it is preferred that a photopolymerization initiator is contained in the hard coat layer. As the amount of the photopolymerization initiator, it is preferably contained in the range of photopolymerization initiator:active radiation curing resin = 20:100 to 0.01:100 in terms of mass ratio. As the photopolymerization initiator, specifically, alkyl phenyl ketones, acetophenone, benzophenone, hydroxybenzophenone, Michler's ketone, α-amyl oxime ester, thioxanthone, etc. and their derivatives can be cited, but it is not particularly limited to these.

[0239] As such a photopolymerization initiator, a commercially available item can be used, and for example, Ilgakuya 184, Ilgakuya 907, Ilgakuya 651, etc. manufactured by BASF Japan Co., Ltd. are mentioned as preferred examples.

[0240] From the viewpoint of improving hard-coating properties and improving the transparency of the optical film, the thickness of the hard-coat layer is preferably in the range of 0.1 to 50 μm, more preferably in the range of 1 to 20 μm.

[0241] The method for forming the hard coat layer is not particularly limited, and examples thereof include a method of preparing a coating solution for forming a hard coat layer containing the above-mentioned components, applying the coating solution using a wire bar, etc., and curing the coating solution with heat or ultraviolet rays to form a hard coat layer.

[0242] From the viewpoint of further improving light resistance and imparting scratch resistance, the hard coat layer preferably contains the compound having a structure represented by the general formula (1) of the present invention, preferably in the range of 0.1 to 40% by mass, more preferably in the range of 0.1 to 20% by mass, relative to the above-mentioned ultraviolet curing resin.

[0243] 〔6〕Polarizing film

[0244] The polarizing plate of the present invention comprises a polarizer and the optical film of the present invention disposed on at least one surface of the polarizer.

[0245] Figure 1 It is a cross-sectional view showing the structure of the polarizing plate 100 .

[0246] like Figure 1 As shown in , the polarizing plate 100 of the present invention can have a polarizer 101, an optical film 102 of the present invention arranged on one surface thereof, an opposing film 103 arranged on the other surface, and two adhesive layers 104 arranged between the polarizer 101 and the optical film 102, and between the polarizer 101 and the opposing film 103.

[0247] (Regarding Polarizer 101)

[0248] The polarizer 101 is an element that transmits only light having a polarization plane in a certain direction, and is a polyvinyl alcohol-based stretched film doped with iodine or a dichroic dye.

[0249] The thickness of the polarizer 101 is in the range of 5 to 40 μm, preferably in the range of 5 to 30 μm, and particularly preferably in the range of 5 to 20 μm.

[0250] (About optical film 102)

[0251] The optical film 102 can function as a retardation film, for example, a λ / 4 retardation film used in a circular polarizing plate of an organic EL image display device.

[0252] In the plane of the optical film 102, the angle formed by the in-plane slow phase axis of the optical film 102 with respect to one side of the rectangular film shape is preferably in the range of 30 to 60 degrees, and more preferably 45 degrees. It should be noted that the above-mentioned side corresponds to the width direction of the long strip of optical film 102. In addition, the angle formed by the in-plane slow phase axis of the optical film 102 and the absorption axis (or transmission axis) of the polarizer 101 is preferably in the range of 30 to 60 degrees, and more preferably 45 degrees.

[0253] Depending on the application, the optical film 102 may also have other layers (for example, a hard coating layer, a low refractive index layer, an anti-reflection layer) arranged on the surface opposite to the polarizer 101. In addition, the optical film 102 may also have an easy-adhesion layer (not shown) arranged on the surface on the polarizer 101 side.

[0254] (Regarding the Opposing Film 103)

[0255] The counter film 103 may be the optical film of the present invention or another optical film (ie, a protective film). More preferably, the optical film of the present invention is used and has a hard coating layer on the outermost surface.

[0256] Examples of commercially available protective films include commercially available cellulose ester films (e.g., Conikaminolta Tak KC8UX, KC5UX, KC4UX, KC8UCR3, KC4SR, KC4BR, KC4CR, KC4DR, KC4FR, KC4KR, KC8UY, KC6UY, KC4UY, KC4UE, KC8UE, KC8UY-HA, KC2UA, KC4UA, KC8UY-HA, KC8 ... C6UA, KC8UA, KC2UAH, KC4UAH, KC6UAH, and the above are manufactured by Knok Mining Co., Ltd., Fukuro T40UZ, Fukuro T60UZ, Fukuro T80UZ、フジタックTD80UL、フジタックTD60UL、フジタックTD 40UL, Fukuro R02, Fukuro R06, and the above manufactured by Fuji Fluoro Co., Ltd.).

[0257] As commercially available cycloolefin-based films, various grades of Zeonoa Film (R), a cycloolefin polymer (COP) molded product manufactured by Zeon Corporation of Japan, are preferably used.

[0258] The thickness of the opposing film 103 may be, for example, in the range of 5 to 100 μm, and preferably in the range of 40 to 80 μm.

[0259] (Regarding Adhesive Layer 104)

[0260] The adhesive layer 104 may be disposed between the polarizer 101 and the optical film 102 , and between the polarizer 101 and the opposing film 103 .

[0261] The adhesive layer 104 may be a layer obtained from a water-based adhesive described later, or may be a cured layer of an ultraviolet curing adhesive.

[0262] The thickness of the adhesive layer 104 is not particularly limited, and is, for example, in the range of 0.01 to 10 μm, and preferably about 0.01 to 5 μm.

[0263] The polarizing plate 100 may be in a long strip shape or in a sheet shape obtained by cutting the long strip polarizing plate in the width direction.

[0264] (physical properties)

[0265] (T1 / T2)

[0266] When the aluminum reflective material is laminated on the optical film of the polarizer via a pressure-sensitive adhesive layer, the reflectance of the polarizer at a wavelength of 460 nm is T1 (%) and the reflectance of the polarizer at a wavelength of 650 nm is T2 (%), the polarizer preferably satisfies the following formula (2).

[0267] Formula (2): 0<T1 / T2<2.6

[0268] If T1 / T2 is less than 2.6, the reflectivity of the light of wavelength 460nm will not be too high, that is, the leakage of the reflected light near this wavelength can be suppressed, so that, for example, the hue of the reflected light in the organic EL image display device can be improved. In addition, if T1 / T2 exceeds 0, for example, the luminescence in the above-mentioned wavelength region in the organic EL image display device is difficult to be hindered by the pigment compound, so the reduction of brightness can be suppressed. T1 / T2 is more preferably less than 2.5.

[0269] (Color difference ΔE(a * b * ))

[0270] In addition, the chromatic aberration ΔE (a * b * ) is preferably less than 25, more preferably less than 20. When the color difference ΔE(a*b*) of the polarizing plate is within the above range, the color tone of reflected light in, for example, an organic EL image display device can be improved.

[0271] T1 / T2 and chromatic aberration ΔE(a * b * ) can be measured according to the following steps.

[0272] 1) An aluminum reflective material was laminated on an optical film of a polarizing plate via a pressure-sensitive adhesive layer to prepare a polarizing plate sample. An acrylic adhesive was used as the pressure-sensitive adhesive.

[0273] 2) The spectral reflectance and color difference ΔE (a* b * ) was measured using a spectrophotometer (CM3700d manufactured by Conika Minolta Co., Ltd.) in accordance with the SCI method.

[0274] T1 / T2 and chromatic aberration ΔE(a * b * ) can be adjusted by the type and content of the pigment compound represented by the general formula (1).

[0275] (Method for Manufacturing Polarizing Plate 100)

[0276] The polarizing plate 100 can be obtained by bonding the polarizer 101 and the optical film 102 of the present invention together via an adhesive. As the adhesive, a water-based adhesive or an ultraviolet curing adhesive is used.

[0277] 〈Water-based adhesive〉

[0278] Examples of the water-based adhesive include water-based adhesives containing a polyvinyl alcohol-based resin (such as a completely saponified polyvinyl alcohol aqueous solution).

[0279] 〈UV-curing adhesive〉

[0280] The ultraviolet curable adhesive composition may be a photo-radical polymerizable composition, a photo-cationic polymerizable composition, or a mixed composition using both of them.

[0281] Examples of the photoradical polymerizable composition include a composition described in Japanese Patent Application Laid-Open No. 2008-009329 that contains a radical polymerizable compound having a polar group such as a hydroxyl group or a carboxyl group and a radical polymerizable compound not having a polar group.

[0282] The free radical polymerizable compound is preferably a compound having an ethylenically unsaturated bond that can be free radically polymerized. Preferred examples of compounds having an ethylenically unsaturated bond that can be free radically polymerized include compounds having a (meth)acryloyl group. Examples of compounds having a (meth)acryloyl group include N-substituted (meth)acrylamide compounds and (meth)acrylate compounds. (Meth)acrylamide refers to acrylamide or methacrylamide.

[0283] Examples of photocationically polymerizable compositions include ultraviolet-curable adhesive compositions disclosed in Japanese Patent Application Laid-Open No. 2011-028234, which include (α) a cationically polymerizable compound, (β) a photocationic polymerization initiator, (γ) a photosensitizer that exhibits maximum absorption at a wavelength longer than 380 nm, and (δ) a naphthalene-based photosensitizing aid.

[0284] The following is an example of using an ultraviolet curing adhesive. The polarizing plate 100 of the present invention can be obtained through the following steps: 1) a step of pre-treating the bonding surfaces of the optical film and the opposing film for easy bonding (pre-treatment step); 2) a step of laminating the polarizer and the optical film (or the opposing film) via an ultraviolet adhesive; and 3) a step of irradiating the laminated product with ultraviolet rays to cure the ultraviolet adhesive (curing step).

[0285] (1) Pre-treatment process

[0286] The adhesion-facilitating treatment is performed on the adhesion surface of the optical film and the polarizer of the opposing film. Examples of the adhesion-facilitating treatment include corona treatment and plasma treatment.

[0287] (2) Lamination process

[0288] The ultraviolet curing adhesive is applied to at least one of the polarizer and the optical film (or the opposing film). There is no particular limitation on the method for applying the ultraviolet curing adhesive, and it may be applied by a scraper, a wire rod, a die coater, a notch wheel coater, a gravure coater, or the like.

[0289] Then, the polarizer is bonded to the optical film or the counter film via an ultraviolet curing adhesive. Then, the two sides of the bonded laminate are sandwiched and pressed with a pressure roller or the like. The material of the pressure roller can be metal or rubber.

[0290] (3) Curing process

[0291] Next, the laminated product bonded via the ultraviolet curing adhesive is irradiated with ultraviolet light to cure the ultraviolet curing adhesive. Thus, the polarizer is bonded to the optical film or the opposing film via the ultraviolet curing adhesive. It should be noted that the curing of the ultraviolet curing adhesive on one side of the polarizer and the curing of the ultraviolet curing adhesive on the other side of the polarizer can be performed sequentially or simultaneously. From the viewpoint of improving the manufacturing efficiency of the polarizer, it is preferred to perform the curing of the ultraviolet curing adhesive on one side of the polarizer and the curing of the ultraviolet curing adhesive on the other side of the polarizer simultaneously.

[0292] The ultraviolet irradiation conditions may be any conditions that allow the ultraviolet curing adhesive to cure. For example, the accumulated light intensity is preferably 50 to 1500 mJ / cm 2 The range is more preferably 100 to 500 mJ / cm 2 range.

[0293] The linear speed during the manufacture of the polarizer depends on the curing time of the adhesive, and is preferably in the range of 1 to 500 m / min, and more preferably in the range of 5 to 300 m / min. If the linear speed is above 1 m / min, it is easy to improve productivity and further reduce damage to the optical film or the opposing film. In addition, if the linear speed is below 500 m / min, the curing of the ultraviolet curing adhesive becomes sufficient, and good adhesion is easily obtained.

[0294] Like this, in the curing process, because ultraviolet irradiation or the heating for promoting curing etc., become high temperature environment sometimes.In addition, even when adhesive is water-based adhesive, because the heating for promoting bonding, the drying of adhesive etc., also become high temperature environment sometimes.

[0295] In contrast, the optical film of the present invention has excellent light resistance and durability, so even in a high temperature environment when the polarizer and the optical film are bonded, a polarizing plate with suppressed light leakage can be obtained. By suppressing light leakage of the polarizing plate, a small amount of light leakage caused by external light reflection during black display can be suppressed in an organic EL image display device having the polarizing plate.

[0296] [7] Image display device

[0297] The optical film of the present invention can be used as an optical film (phase difference film, protective film) for image display devices such as organic EL image display devices and liquid crystal display devices. Among them, the optical film of the present invention can be preferably used as a phase difference film (λ / 4 phase difference film) for organic EL image display devices.

[0298] 〔7.1〕Organic EL image display device

[0299] Figure 2 is an exploded cross-sectional view of the organic EL image display device 200 .

[0300] The organic EL image display device 200 includes an organic EL element 300 (display unit), a polarizing plate 100 (circular polarizing plate), and an adhesive layer 400 disposed therebetween.

[0301] The organic EL element 300 has a metal electrode 302, a light emitting layer 303, a transparent electrode (ITO or the like) 304, and a sealing layer 305 in this order on a substrate 301 such as glass or polyimide. The metal electrode 302 may be composed of a reflective electrode and a transparent electrode.

[0302] The metal electrode 302 can function as a cathode. In order to facilitate electron injection and improve light emission efficiency, the metal electrode 302 is preferably made of a material with a small work function, and Mg-Ag or Al-Li is generally used.

[0303] The light-emitting layer 303 is a stack of organic thin films, for example, it can be a stack of a hole injection layer composed of a triphenylamine derivative and a light-emitting layer composed of a fluorescent organic solid such as anthracene, a stack of such a light-emitting layer and an electron injection layer composed of a perylene derivative, a stack of these hole injection layers, light-emitting layers, and electron injection layers, etc.

[0304] The transparent electrode 304 can function as an anode and can be generally made of a transparent conductor such as indium tin oxide (ITO).

[0305] Then, by applying a voltage between the metal electrode 302 and the transparent electrode 304, holes and electrons are injected into the light-emitting layer 303, and the energy generated by the recombination of these holes and electrons excites the fluorescent material, and when the excited fluorescent material returns to the ground state, it radiates light and emits light.

[0306] The polarizing plate 100 is disposed on the visible side surface of the organic EL element 300. The polarizing plate 100 is the polarizing plate 100 described above (see Figure 1 ), the optical film 102 (λ / 4 phase difference film) is arranged between the organic EL element 301 and the polarizer 101. As for the angle formed by the transmission axis (or absorption axis) of the polarizer 101 and the in-plane lag axis of the optical film 102, as described above, they are preferably bonded in a manner of 45° (or 135°).

[0307] The opposing film 103 preferably further has a hard coating layer (not shown) disposed on its visible side surface (the surface opposite to the polarizer 101). The hard coating layer not only prevents damage to the surface of the organic EL image display device, but also reduces the warping of the polarizer 100. In addition, an antireflection layer may be further formed on the hard coating layer.

[0308] The adhesive layer 400 is disposed between the organic EL element 300 and the polarizer 100 to bond them. Examples of the adhesive constituting the adhesive layer 400 include thermosetting adhesives (epoxy thermosetting adhesives, urethane thermosetting adhesives, acrylic thermosetting adhesives, etc.), hot melt adhesives, etc. (rubber hot melt adhesives, polyester hot melt adhesives, polyolefin hot melt adhesives, ethylene-vinyl acetate resin hot melt adhesives, polyurethane resin hot melt adhesives, etc.).

[0309] (effect)

[0310] In such an organic EL image display device 200, when a voltage is applied to the metal electrode 302 and the transparent electrode 304, electrons are injected from the metal electrode 302 serving as a cathode into the light-emitting layer 303, and holes are injected from the transparent electrode 304 serving as an anode, and the two are recombined in the light-emitting layer 303, thereby generating visible light corresponding to the light-emitting characteristics of the light-emitting layer 303. The light generated in the light-emitting layer 303 is directly or reflected by the metal electrode 302, and then taken out to the outside through the transparent electrode 304 and the polarizing plate 100.

[0311] The light-emitting layer 303 is formed of an extremely thin film having a thickness of about 10 nm. Therefore, the light-emitting layer 303 also transmits light almost completely, similarly to the transparent electrode 304. As a result, light that enters from the outside of the organic EL image display device 200 and passes through the sealing layer 305, the transparent electrode 304, and the light-emitting layer 303 to reach the metal electrode 302 in the non-luminescent state is reflected by the metal electrode 302, and again passes through the light-emitting layer 303, the transparent electrode 302, and the sealing layer 305 to exit toward the surface side of the organic EL device 200. At this time, the optical film 102 suppresses the light reflected by the metal electrode 302 from leaking toward the surface side of the organic EL image display device 200, thereby reducing external light reflection.

[0312] That is, when not emitting light, half of the external light incident from the outside of the organic EL image display device 200 by indoor lighting or the like is absorbed by the polarizer 101 of the polarizing plate 100, and the remaining half is not absorbed and is transmitted as linearly polarized light, and is incident on the optical film 102 (λ / 4 phase difference film). The light incident on the optical film 102 is converted into circularly polarized light because the transmission axis of the polarizer 101 and the in-plane lag axis of the optical film 102 intersect at 45° (or 135°).

[0313] The circularly polarized light emitted from the optical film 102 is phase-reversed 180 degrees and becomes counter-rotating circularly polarized light when it is specularly reflected by the metal electrode 302 of the organic EL element 300. The reflected light is converted into linearly polarized light perpendicular to the transmission axis (parallel to the absorption axis) of the polarizer 101 by entering the optical film 102, and is therefore absorbed by the polarizer 101 and can be suppressed from being emitted to the outside.

[0314] Furthermore, in the present invention, an optical film 102 containing a specific pigment compound is used. Thus, the optical film 102 can convert light in a specific wavelength region (which cannot be converted into the desired linear polarized light for a cycloolefin resin film not containing a pigment compound) into linear polarized light perpendicular to the transmission axis of the polarizer 101 (parallel to the absorption axis). Thus, it is possible to suppress the reduction in the hue of the reflected light caused by the reflected light in the specific wavelength region leaking through the transmission axis of the polarizer 101. In addition, even if the optical film 102 contains a pigment compound, it has excellent light resistance, and it is also possible to suppress the display unevenness caused by this.

[0315] Example

[0316] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that "parts" or "%" are used in the examples, but unless otherwise specified, they represent "parts by mass" or "mass %".

[0317] [Example 1]

[0318] 1. Optical film materials

[0319] (1) Cycloolefin resin

[0320] 《Synthesis of Cycloolefin Resin 1》

[0321] 100 parts by mass of purified toluene and 100 parts by mass of methyl norbornene carboxylate (see the following structural formula A) are placed in a reactor. Next, 25 mmol% (to the monomer mass) of ethyl hexanoate-Ni dissolved in toluene, 0.225 mol% (to the monomer mass) of tri(pentafluorophenyl)boron, and 0.25 mol% (to the monomer mass) of triethylaluminum dissolved in toluene are placed in a reactor and reacted for 18 hours while stirring at room temperature. After the reaction is completed, the reaction mixture is added to an excess of ethanol to generate a polymer precipitate. The precipitate is purified, and the obtained solid is dried at 65°C for 24 hours by vacuum drying to obtain a cycloolefin resin (P-1) (weight average molecular weight Mw: 140,000, Tg: 140°C). It should be noted that the weight average molecular weight is measured by the above method.

[0322] [Chemistry 17]

[0323] Structural Formula A

[0324]

[0325] (2) Pigment compounds

[0326] The exemplary dye compounds and comparative compounds described in Table 1 were prepared, and the HOMO energy level (eV) was calculated.

[0327] Regarding the calculation of the HOMO energy level of the illustrative pigment compound and the comparative compound having the structure represented by the general formula (1) by molecular orbital calculation, as a calculation method, it can be calculated using a molecular orbital calculation software using B3LYP as a universal function and 6-31G(d) as a basis function. There is no particular limitation on the software, and the result can be obtained in the same manner using any one of them.

[0328] In the present invention, the calculation was performed using Gaussian09 (Revision C.01, MJ Frisch et al., Gaussian, Inc., 2010.) manufactured by Gaussian, Inc., USA as a software for molecular orbital calculation. Table I shows the values ​​of HOMO energy levels of the calculation results.

[0329] "Synthetic Examples of Illustrated Pigment Compounds"

[0330] <Exemplary dye compound 9>

[0331] [Chemistry 18]

[0332]

[0333] In a 100mL three-necked flask, 1g of compound (9-1) and 0.277g of malononitrile were measured, 18mL of toluene was added and dissolved. Then, 0.332g of morpholine was added dropwise, the temperature was raised, and heated to reflux for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, 5mL of methanol was added, and stirred in a suspended state. The precipitate was filtered and dried to obtain 0.33g (yield 28%) of powder of the illustrative pigment compound 9. The structure was confirmed by NMR.

[0334] <Exemplary dye compound 23>

[0335] [Chemistry 19]

[0336]

[0337] In a 100mL three-necked flask, 1g of compound (23-1) and 0.497g of malononitrile were measured, 40mL of toluene was added and dissolved. Then, 0.596g of morpholine was added dropwise, the temperature was raised, and heated to reflux for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, 5mL of methanol was added, and stirred in a suspended state. The precipitate was filtered and dried to obtain 0.24g (yield 18%) of powder of the illustrative pigment compound 23. The structure was confirmed by NMR.

[0338] [Chemistry 20]

[0339]

[0340] (Determination of absorption maximum wavelength)

[0341] The absorption maximum wavelengths of the above compounds were determined by measuring the absorption spectra of the dye compounds in dichloromethane using an ultraviolet-visible spectrophotometer UV-2450 manufactured by Shimadzu Corporation, and are shown in Table II.

[0342] In addition, the "absorption maximum wavelength" in the present invention refers to a wavelength (nm) showing the maximum and highest absorbance (absorption intensity) in the absorption spectrum of the compound obtained when the absorption spectrum of the compound is measured.

[0343] [Table 1]

[0344] Table I

[0345] Exemplary pigment compound No. Calculated value of HOMO energy level (eV) 1 -7.45 3 -5.83 6 -6.48 8 -5.89 9 -6.30 12 -5.98 23 -6.52 24 -6.42 29 -6.16 38 -6.40 39 -6.18 40 -6.28 Comparative Compound 1 -5.61 Comparative Compound 2 -5.85 Comparative Compound 3 -5.72

[0346] [Table 2]

[0347] Table II

[0348] Exemplary pigment compound No. Absorption maximum wavelength (nm) 9 361 12 416 39 406 40 415

[0349] 2. Production and evaluation of optical films

[0350] <Production of Optical Film 101>

[0351] (Preparation of microparticle additive solution)

[0352] The following components were stirred and mixed for 50 minutes using a dissolver, and then dispersed using a Manton-Gaulin. Furthermore, the secondary particles were dispersed using a grinder in such a way that the particle size became a predetermined size. The particles were filtered using a NF filter manufactured by Nippon Seisen Co., Ltd. to prepare a microparticle additive solution.

[0353] Microparticles (Aerosil R812: manufactured by Aerosil Japan, primary average particle size: 7 nm, apparent specific gravity: 50 g / L): 4 parts by mass

[0354] Dichloromethane: 48 parts by mass

[0355] Ethanol: 48 parts by mass

[0356] (Preparation of glue)

[0357] The following components were placed in a sealed container while being thoroughly stirred, and the temperature was raised to 80° C. and maintained for 1 hour. Then, the mixture was cooled to 30° C. and filtered through a filter with a pore size of 5 μm to obtain dope A-1.

[0358]

[0359] (Production of Optical Film 101)

[0360] On a ring-shaped metal support driven at a speed of 30 m / min, the prepared slurry is cast from the casting die, and a dry wind of 40°C is irradiated on the support to dry it until a self-supporting cast film (membrane-like object) is obtained. Then, it is cooled to 10°C and the cast film is peeled off from the support. Then, after the peeled cast film is dried at 110°C for 30 minutes, it is stretched at 170°C in a direction (inclined direction) of 45° relative to the width direction with a stretching ratio of 2 times. Thus, an optical film 101 with a film thickness of 40 μm having an in-plane lag axis in a direction of about 45° relative to the width direction is obtained.

[0361] The optical film 101 was confirmed to have a retardation value Ro of 145 nm by the above-mentioned retardation value evaluation method, and was confirmed to be a film functioning as a λ / 4 plate.

[0362] <Production of Optical Films 102 to 119>

[0363] In the production of the optical film 101 , the optical films 102 to 119 were produced in the same manner except that the exemplary dye compounds were changed as described in Table III.

[0364] "evaluate"

[0365] <Light transmittance>

[0366] The light transmittance was measured using a spectrophotometer (U-3300 manufactured by Hitachi HiTech Science) in accordance with JIS K 7375:2008 "Plastics - Methods for determining total light transmittance and total light reflectance". A light transmittance of 80% or more was evaluated as "○", and a light transmittance of less than 80% was evaluated as "△".

[0367] <Light resistance test>

[0368] The optical film produced as described above was subjected to a light resistance test.

[0369] The prepared film was irradiated with a xenon lamp (60 W / m 2 ) light, and measured the absorbance of the film before irradiation (0 hour) and after irradiation (100 hours) with a spectrophotometer, and the pigment residual rate was determined according to the following formula (1).

[0370] Formula (1) Pigment residual rate (%) = {(A 100 ) / (A0)}×100

[0371] (Where A0 is the absorbance before xenon lamp irradiation, A 100 is the absorbance after irradiation with a xenon lamp.)

[0372] It should be noted that "absorbance" refers to the absorbance at the absorption maximum wavelength of each compound, and the higher the residual rate of the pigment, the more difficult the compound is to be decomposed by light and the higher the light resistance. The light resistance was evaluated according to the following criteria.

[0373] A: Pigment residual rate is more than 65%

[0374] B: Pigment residual rate is 40% or more and less than 65%

[0375] C: Pigment residual rate is 10% or more and less than 40%

[0376] D: Pigment residual rate is less than 10%

[0377] <Durability: Evaluation of seepage>

[0378] Each optical film was left in a high temperature and high humidity atmosphere of 60° C. and 90% RH for 1000 hours, and then visually observed for the presence or absence of bleed (crystallization) on the surface of the optical film. The bleed was evaluated according to the following criteria.

[0379] ◎: No bleeding was found on the surface of the optical film

[0380] ○: Slight bleeding was observed on the optical film surface

[0381] △: Slight bleeding was observed on the entire surface of the optical film.

[0382] ×: On the surface of the optical film, obvious bleeding was observed over the entire surface.

[0383] The configuration of the optical film and the above evaluation results are shown in Table III.

[0384] [Table 3]

[0385] Table III

[0386]

[0387] As can be seen from the results in Table III, the optical film of the present invention is excellent in light transmittance, light resistance and durability by using the pigment compound having a structure represented by the general formula (1) according to the present invention.

[0388] [Example 2]

[0389] <Production of Optical Film 201>

[0390] 19.7 parts by mass of urethane acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., UA-1100H), 0.1 parts by mass of photopolymerization initiator (Ilgacur 184 manufactured by BASF), 0.3 parts by mass of modified silicone (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.), 0.05 parts by mass of Emulgen 404 (manufactured by Kao Chemical Co., Ltd.), 39.5 parts by mass of propylene glycol monomethyl ether (PGME), 39.5 parts by mass of methyl acetate, and 0.1 parts by mass of the exemplary pigment compound 6 were mixed and stirred thoroughly to prepare a coating composition. The obtained coating composition was applied to a 25 μm thick COP substrate with a wire rod and then dried and UV cured to manufacture an optical film 201 having a functional layer (hard coat) with a thickness of 5 μm.

[0391] <Production of Optical Films 202 to 212>

[0392] In the production of the optical film 201 , the optical films 202 to 212 were produced in the same manner except that the exemplary pigment compounds were changed as described in Table IV.

[0393] The light resistance and durability of the produced optical films 201 to 212 were evaluated in the same manner as in Example 1. The results are shown in Table IV.

[0394] [Table 4]

[0395] Table IV

[0396]

[0397] As can be seen from the results in Table IV, the optical film of the present invention has excellent light transmittance, light resistance and durability as in Example 1 by using the compound having a structure represented by the general formula (1) of the present invention in the functional layer.

[0398] [Example 3]

[0399] Using the optical films produced in Examples 1 and 2, polarizing plates were produced and evaluated.

[0400] <Preparation of Polarizing Plate 301>

[0401] (1) Preparation of polarizer

[0402] A long polyvinyl alcohol film with a thickness of 60 μm was continuously conveyed via a guide roller and immersed in a dyeing bath (30°C) mixed with iodine and potassium iodide. After dyeing treatment and 2.5-fold stretching treatment were performed, a total of 5-fold stretching treatment and cross-linking treatment were performed in an acidic bath (60°C) added with boric acid and potassium iodide. The obtained iodine-PVA polarizer with a thickness of 12 μm was dried in a dryer at 50°C for 30 minutes to obtain a polarizer with a moisture content of 4.9%.

[0403] (2) Preparation of UV-curable adhesive

[0404] The following components were mixed to obtain a liquid ultraviolet curing adhesive (UV adhesive).

[0405] 3,4-Epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate: 40 parts by mass

[0406] Bisphenol A epoxy resin: 60 parts by mass

[0407] Diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate (cationic polymerization initiator):

[0408] 4 parts by mass

[0409] (3) Preparation of polarizer

[0410] After the bonding surface of the optical film 101 was subjected to corona treatment, the prepared ultraviolet curing adhesive was applied to the bonding surface in a manner of 3 μm in dry thickness using a coating device equipped with a chamber scraper. In addition, similarly, the bonding surface of Conika Minolta KC4CT (thickness 40 μm, manufactured by Conika Minolta Co., Ltd.) as an opposing film was subjected to corona treatment, and the ultraviolet curing adhesive was applied to the bonding surface in a manner of 3 μm in dry thickness.

[0411] Then, the optical film 101 is immediately bonded to one side of the polarizer produced above via an ultraviolet curing adhesive in a roll-to-roll manner, and a TAC film as a counter film is bonded to the other side via an ultraviolet curing adhesive. The bonding is performed in a manner that the lag axis (or advance axis) of the optical film 101 is consistent with the absorption axis (or transmission axis) of the polarizer (in a manner that the angle formed by the in-plane lag axis of the optical film 101 and the absorption axis of the polarizer is 45°). Then, while conveying the bonded product at a linear speed of 20 m / min, ultraviolet rays are irradiated from the optical film 106 side using a metal halide lamp so that the accumulated light amount with a wavelength of 280 to 320 nm becomes 320 mJ / cm 2 Thus, the ultraviolet curable adhesive is cured to obtain the polarizing plate 301. It should be noted that the production of the polarizing plate 301 is carried out by a roll-to-roll method, so the long strip of polarizing plate is finally cut along the width direction to obtain the sheet-shaped polarizing plate 301.

[0412] The prepared polarizing plate 301 was bonded to a portion of a commercially available organic EL image display device from which the polarizing plate on the visible side was peeled off, so that the optical film 101 side of the polarizing plate became the organic EL element side, thereby preparing the organic EL image display device 301 .

[0413] <Production of Polarizing Plate and Organic EL Image Display Devices 302 to 319>

[0414] In the production of the polarizing plate 301 , except that the optical film 101 was changed as described in Table V, the polarizing plates 302 to 319 and the organic EL image display devices 302 to 319 were produced in the same manner.

[0415] The same evaluation as in Example 1 and the following light leakage evaluation were performed on the produced polarizing plates 301 to 319 and the organic EL image display devices 301 to 319. The results are shown in Table V.

[0416] <Light leakage evaluation>

[0417] The organic EL image display device produced as described above was stored in an environment of 60°C and 90% RH for 500 hours, and then placed at normal temperature and humidity (23°C and 55% RH) for 24 hours. The occurrence of display unevenness caused by light leakage from the screen during black display was visually observed in a dark room and evaluated according to the following standards.

[0418] ○: No display unevenness caused by light leakage

[0419] △: Display unevenness due to light leakage is slightly observed

[0420] ×: Display unevenness due to obvious light leakage

[0421] [Table 5]

[0422] Table V

[0423]

[0424] As can be seen from Table V, by using the optical film of the present invention, a polarizing plate and an organic EL image display device having excellent light resistance and durability and having no light leakage can be obtained.

[0425] Industrial Applicability

[0426] The optical film of the present invention has high transparency, prevents light leakage, and is excellent in light resistance and durability under severe environmental conditions. Therefore, the optical film can be suitably used in polarizing plates and organic electroluminescent image display devices.

[0427] Description of Reference Numerals

[0428] 100 Polarizer

[0429] 101 Polarizer

[0430] 102 Optical Film

[0431] 103 Opposing film

[0432] 104 Adhesive layer

[0433] 200 Organic EL image display device

[0434] 300 Organic EL components

[0435] 301 substrate

[0436] 302 Metal Electrode

[0437] 303 Luminous Layer

[0438] 304 Transparent Electrode

[0439] 305 Sealing layer

[0440] 400 Adhesive layer

Claims

1. An optical film comprising a thermoplastic resin, characterized in that: Containing: a compound having a structure represented by the following general formula (1), The energy level of the highest occupied orbital of the compound having the structure represented by the general formula (1) is -5.85 eV or less, General formula (1) In the formula, Z is any group represented by the following structural formula, The thermoplastic resin is a cyclic olefin resin or an acrylic resin. The cyclic olefin resin has a polar group. The group represented by the above structural formula may further have a substituent, and R represents a substituent.

2. The optical film according to claim 1, characterized in that: Furthermore, Z is any group represented by the following structural formula: The group represented by the above structural formula may further have a substituent, and R represents a substituent.

3. The optical film according to claim 1 or 2, characterized in that: The compound having a structure represented by the general formula (1) is contained in an amount within a range of 0.01 to 20% by mass based on the thermoplastic resin.

4. The optical film according to claim 1 or 2, characterized in that: It also has a functional layer.

5. The optical film according to claim 4, characterized in that: The functional layer contains the compound having a structure represented by the general formula (1).

6. The optical film according to claim 1 or 2, characterized in that: The optical film is a λ / 4 phase difference film.

7. A polarizing plate, characterized in that: The invention comprises: the optical film according to any one of claims 1 to 6.

8. An organic electroluminescent image display device, characterized in that: The invention comprises: the optical film according to any one of claims 1 to 6 or the polarizing plate according to claim 7.

Citation Information

Patent Citations

  • Retardation film, polarizing plate and liquid crystal display element using the same

    JP2005227606A

  • Polarizing plate and method for manufacturing the same

    JP2008009329A

  • Optical film, manufacturing method of optical film, retardation film, polarizing plate and liquid crystal panel

    JP2008107534A

  • Heat-resistant acrylic resin composition and molding thereof

    JP2011026563A

  • Polarizing plate and laminated optical member using the same

    JP2011028234A